PROBLEMA KEBIJAKAN PENGELOLAAN KEUANGAN DAERAH YANG BERIMPLIKASI PIDANA ADMINISTRASI YANG BERDAMPAK PADA UU NOMOR 20 TAHUN 2001 TENTANG TINDAK PIDANA KORUPSI - Sugianto Sugianto (UIN Siber Syekh Nurjati Cirebon, 2019)
AbstractThe issue of regional autonomy policy gives very broad autonomy to the district/city government, but in reality, it cannot be realized by the law. The purpose of the roll out of regional autonomy in order to restore the dignity of the people in the region by providing opportunities for political education in the context of improving the quality of democracy in the region, increasing the efficiency of public services in the region, and creating good governance. The extent to which the Central Government in building synergy and harmonization with the Kewrahab / city Regional Government in Indonesia